Modified hydroxyapatite improves the corrosion resistance of the epoxy coating. Issue 37 (23rd July 2022) - Peng, Bokai; Yu, Zongxue; Chen, Legang; Liao, Kexi; Chen, Haidong; Guo, Yuchi; Liu, Yucheng
Abstract: In this study, HAp(hydroxyapatite) was prepared by hydrothermal method and was successfully modified by APTES (aminopropyltriethoxysilane) to obtain APTES‐HAp nanomaterial. Firstly, the microstructure and surface morphology of HAp and APTES‐HAp were studied by Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), and scanning electron microscope (SEM), and it was confirmed that HAp and APTES‐HAp composites were successfully synthesized. Secondly, SEM analysis is used to study the dispersion of APTES‐HAp in epoxy resin, and it is proved that the dispersion of HAp modified by APTES is greatly improved. Finally, the corrosion resistance of the composite coating was studied in detail by electrochemical impedance spectroscopy (EIS). The results show that the APTES‐HAp /EP composite coating impedance modulus remains 10 7 . The breakpoint frequency (fb ) is always the minimum after 30 days of immersion, which proves that the corrosion resistance of APTES‐HAp /EP composite coating is significantly improved APTES‐HAp/EP. The improvement of corrosion resistance is mainly attributed to the following two points: APTES‐HAp has good uniform dispersion and interfaces compatibility in epoxy resin, forming an effective barrier network. On the other hand, layered HAp forms physical barriers and maze effects on corrosive media. Abstract :